2018
DOI: 10.1038/s41408-018-0078-3
|View full text |Cite
|
Sign up to set email alerts
|

The Aspirin Regimens in Essential Thrombocythemia (ARES) phase II randomized trial design: Implementation of the serum thromboxane B2 assay as an evaluation tool of different aspirin dosing regimens in the clinical setting

Abstract: Once-daily (od), low-dose aspirin (75–100 mg) is recommended to reduce the thrombotic risk of patients with essential thrombocytemia (ET). This practice is based on data extrapolated from other high-risk patients and an aspirin trial in polycythemia vera, with the assumption of similar aspirin pharmacodynamics in the two settings. However, the pharmacodynamics of low-dose aspirin is impaired in ET, reflecting accelerated renewal of platelet cyclooxygenase (COX)-1. ARES is a parallel-arm, placebo-controlled, ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 50 publications
2
43
0
Order By: Relevance
“…The protocol was approved by the Institutional Ethics Committee (approval P/852/CE/2012). Nonobese (BMI of <30 kg/m 2 ) healthy controls were chosen from a large database of previously published cohorts of healthy volunteers, receiving or not receiving aspirin for 3‐5 weeks to match 1:1 with obese subjects for sex and age.…”
Section: Methodsmentioning
confidence: 99%
“…The protocol was approved by the Institutional Ethics Committee (approval P/852/CE/2012). Nonobese (BMI of <30 kg/m 2 ) healthy controls were chosen from a large database of previously published cohorts of healthy volunteers, receiving or not receiving aspirin for 3‐5 weeks to match 1:1 with obese subjects for sex and age.…”
Section: Methodsmentioning
confidence: 99%
“…Petrucci et al (2016) investigated whether a variable delay in 37°C incubation and/or analytical discrepancies may affect the assessment of aspirin pharmacodynamics based on serum TXB 2 determinations. They found that a longer than 5-min delay in the 37°C incubation of whole-blood samples may variably influence the assessment of platelet COX-1 inhibition by low-dose aspirin and confound the analysis of aspirin responsiveness in the clinical setting (Petrucci et al, 2016; De Stefano et al, 2018). In contrast, a GC/MS-validated immunoassay and liquid chromatography-tandem mass-spectrometry yielded quite comparable TXB 2 concentrations in the same serum samples (Petrucci et al, 2016).…”
Section: Serum Txb2 As a Validated Index Of Platelet Cox-1 Activitymentioning
confidence: 99%
“…Serum TXB 2 and urinary 2,3-dinor-6-keto-PGF 1a 60 are the most attainable biomarkers to test the adequacy of platelet COX-1 inactivation and sparing of endothelial COX-2, respectively, throughout a variable dosing interval of aspirin in the low-dose range. Recently, the design of a prospective study to find the most appropriate schedule of LDA based on biological biomarker modifications has been published and results are awaited soon 61 .…”
Section: Resultsmentioning
confidence: 99%